Binary pore structure and fractal characteristics of tight sandstone： A case study of Chang 7 Member of Triassic Yanchang Formation in Ordos Basin - WU Xiaobin; DU Zhiwen; QIANG Xiaolong; LEI Tian; JIANG Tingting; WANG Wei; ZHU Yushuang (Youqi dizhi yu caishoulu)
The pore structure characteristics of tight sandstone are of significance for the exploration and development of tight oil reservoirs. However， little attention is paid to the flow characteristics and influencing factors of different types of pores. This restricts the understanding of the flow and storage capacity of tight sandstone and affects the evaluation and prediction of favorable areas for tight oil reservoirs. Therefore， this paper focuses on the tight sandstone in the Chang 7 member of the Triassic Yanchang Formation in Ordos Basin， and casting thin sections， scanning electron microscopy， nuclear magnetic resonance， and the fractal method are adopted to research the pore structure characteristics of tight sandstone. The results indicate that the pore structure of tight sandstone is a binary pore system composed of bound pores and movable pores. The morphological characteristics and connectivity of different types of pores vary greatly. Bound pores are mainly composed of intergranular pores， and the pore model is the envelope surface of clay accumulation. The pore radius is small， the connectivity is poor， and the fluid flow is poor. The pore features a regular shape， weak heterogeneity， low fractal dimension， and an average value of 1.306 3. The movable pores are mainly combined pores with a spiky-spherical shape. This type of pore has a large radius and multiple connecting channels formed by dissolution， resulting in strong connectivity. The shape of movable pores is irregular， with strong heterogeneity， a large fractal dimension， and an average value of 3.241 6. The influence of different types of pores on physical properties is also different. The average contribution of bound pores to porosity is 47.7%， and that of movable pores to porosity is 52.3%. The two types of pores have similar content but are affected by differences in connectivity. The average contribution of bound pores to permeability is 0.2%， while that of movable pores to permeability is 99.8%. Movable pores are the main factor affecting the permeability of tight sandstone. The fractal dimension can characterize the pore structure of tight sandstone. Sandstone is mainly composed of composite pores and located near the source rocks is a favorable area for exploration and development of tight sandstone.